High Sugar Production from Hydrolysate of Pineapple Residues via Integrated Enzyme‐Membrane System. Issue 10 (25th August 2022) - Ayanasamy, Kohmalam; Baharudin, Aishah; Jamek, Shariza; Saufi, Syed M.; Hairom, Nur Hanis Hayati; Mohd Sueb, Mohd Shafiq
Abstract: The enzyme‐membrane integrated system has become an attractive method for the depolymerization of lignocellulosic biomass. The effects of pH, temperature, enzyme loading, and reaction time were evaluated in order to maximize the sugar production. Hydrolysate extracted from pineapple leaves was used as a substrate. The feed substrate was hydrolyzed by β ‐xylosidase under different working conditions using the one‐factor‐at‐a‐time (OFAT) method. The best working conditions obtained via enzymatic hydrolysis were applied in the enzyme‐membrane integrated system. The sugar yield obtained by simultaneous reaction and filtration was much higher (293.94 %) than by the reaction alone (32.23 %). Abstract : The proposed enzyme‐membrane integrated system creates an effective way of simultaneously retaining sugar and enzyme recovery. The optimum conditions for maximum reducing sugar production using enzymatic hydrolysis (reaction only) were evaluated and the obtained results were compared to those of an enzyme‐membrane integrated system, i.e., simultaneous reaction and filtration.